Morocco : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This Selected Issues paper for Morocco discusses possible fiscal policy anchors, specifically deficit targets, and the sustainability of the resulting fiscal paths. Morocco has made great progress toward fiscal consolidation in recent years, under the combined effect of a strong revenue performance and efforts to tackle expenditure rigidities, notably the wage bill. Morocco's low social indicators and large infrastructure needs could justify an increase in social spending and public investment. Morocco's fiscal performance lags that of the better-rated emerging market economies.